(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
Architectural design holds a pivotal role in shaping the development of university campuses. This study critically examines the extent to which the architectural plans of four campuses correspond with the conceptual framework of an educational campus. The evaluation of design quality is crucial, as it significantly influences both academic and non-academic environments, thereby contributing to the overall enhancement of higher education quality. Adopting a mixed methods research (MMR) approach, the initial phase employs the Analytic Hierarchy Process (AHP) to establish the Priority Design Principles for Educational Campuses. Subsequently, the quantitative phase focuses on formulating a decision-making model to assess the quality of the educational atmosphere through the application of a fuzzy logic system. The findings of this research reveal that the top three design criteria, identified as having the highest priority, serve as the basis for developing a comprehensive model to evaluate campus designs grounded in the educational campus paradigm. These three key criteria functions as benchmarks for determining whether a campus’s architectural design satisfies the essential standards of an educational campus. An empirical assessment conducted across four university campuses indicates that only the campus design of Malikussaleh University falls short of meeting the educational campus design criteria. In contrast, the remaining three universities have successfully adhered to the principles underpinning the educational campus concept.